The Crime Of Cessie Forgery In Bank - Fauzi, Muhammad Raka; Hilman, didi; Lestari, Nisa (Universitas Ibn Khaldun Bogor, 2025)
Forgery, regardless of the situation or location within a country, constitutes a criminal act that is unequivocally subject to the prevailing legal regulations. This type of misconduct is frequently perpetrated by individuals prioritizing personal gain without considering the long-term consequences of their actions. One common form of forgery observed in the professional world is the falsification of cessie in banking institutions. Banks, being entities that extensively handle personal data such as identification and other sensitive information, are particularly vulnerable to exploitation by unscrupulous individuals. One example of this is the forgery of a bank product known as cessie. A cessie refers to a debtor's receivable that cannot be repaid or continued due to the inability to pay installments. The receivable is then transferred to a cessier or recipient who assumes responsibility for continuing the installment payments. Given such a susceptible situation, it becomes crucial for customers and the public to better understand the concepts involved in any dealings they undertake. Additionally, all parties involved must exercise greater caution and thoroughness to prevent such acts from being carried out by irresponsible individuals.